2021
DOI: 10.3390/microorganisms9040724
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis on the Mechanism of Ethylicin Inhibiting Pseudomonas syringae pv. actinidiae on Kiwifruit

Abstract: Bacterial canker disease caused by Pseudomonas syringae pv. actinidiae (Psa) is a devastating disease of kiwifruit, which is severely limiting the development of the kiwifruit industry. Ethylicin is a broad-spectrum plant biomimetic fungicide. However, its application in the control of kiwifruit bacterial canker is rarely reported, and the mechanism of ethylicin on Psa remains unknown. In this study, we investigated the effect of ethylicin on Psa in vitro and in vivo and found that ethylicin can inhibit the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…30 Briefly, 5 mL of Xoc (OD 595 = 0.6) was treated with ethylicin at concentrations of 1.10, 2.12, and 4.24 μg/mL, the 50 μg/ mL SC functioning as the positive control and not added as a negative control. The medium was kept at 28 °C for 5 days, removed, and then washed twice with distilled water before being stained for 15…”
Section: = × I C I Antibacterial Activity (%) ( )/ 100%mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Briefly, 5 mL of Xoc (OD 595 = 0.6) was treated with ethylicin at concentrations of 1.10, 2.12, and 4.24 μg/mL, the 50 μg/ mL SC functioning as the positive control and not added as a negative control. The medium was kept at 28 °C for 5 days, removed, and then washed twice with distilled water before being stained for 15…”
Section: = × I C I Antibacterial Activity (%) ( )/ 100%mentioning
confidence: 99%
“…actinidiae and prevent kiwifruit stem, can significantly upregulate protein export and biofilm formation genes, and significantly downregulate flagellar assembly-related genes by transcriptomics. 15 Because of the lack of reports on the use of ethylicin to control BLS, the mechanisms of its action on Xoc are still unclear. The results presented in this paper show that ethylicin is effective against Xoc both in vitro and in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mechanically, studies have shown that ET could disrupt the cell membrane and flagella formation in Pseudomonas syringae pv. Actinidiae through transcriptomics and electron microscopy . The expression of amino acids, apoptosis-inducing factors, and virulence-related genes in Phytophthora nicotianae was disorganized under the combination of ET and melatonin .…”
Section: Introductionmentioning
confidence: 99%
“…Actinidiae through transcriptomics and electron microscopy. 18 The expression of amino acids, apoptosis-inducing factors, and virulence-related genes in Phytophthora nicotianae was disorganized under the combination of ET and melatonin. 19 Proteomic and metabolomic studies have shown that ET can inhibit ribosome function and amino acid metabolism of Phytophthora infestans, thus inhibiting protein synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kiwifruit ( Actinidia deliciosa ) is a berry fruit belonging to the Actinidiaceae family and it is rich in vitamin C and a variety of mineral elements [ 1 , 2 ]. Kiwifruit is often infected by plant pathogens, causing its food value and economic value to be seriously damaged by diseases, including soft rot, bacterial canker, and crown gall disease [ 3 , 4 , 5 , 6 ]. The pathogenic bacteria in Agrobacterium spp.…”
Section: Introductionmentioning
confidence: 99%